DNA damage signatures in peripheral blood cells as biomarkers in prodromal huntington disease. Issue 2 (13th January 2019) - Castaldo, Imma; De Rosa, Mariarosaria; Romano, Antonella; Zuchegna, Candida; Squitieri, Ferdinando; Mechelli, Rosella; Peluso, Silvio; Borrelli, Cristiana; Del Mondo, Angelo; Salvatore, Elena; Vescovi, Luigi Angelo; Migliore, Simone; et al.
Abstract : Easily accessible biomarkers in Huntington disease (HD) are actively searched. We investigated telomere length and DNA double‐strand breaks (histone variant pγ‐H2AX) as predictive disease biomarkers in peripheral blood mononuclear cells (PBMC) from 25 premanifest subjects, 58 HD patients with similar CAG expansion in the huntingtin gene ( HTT ), and 44 healthy controls (HC). PBMC from the pre‐HD and HD groups showed shorter telomeres ( p < 0.0001) and a significant increase of pγ‐H2AX compared to the controls ( p < 0.0001). The levels of pγ‐H2AX correlated robustly with the presence of the mutated gene in pre‐HD and HD. The availability of a potentially reversible biomarker (pγ‐H2AX) in the premanifest stage of HD, negligible in HC, provides a novel tool to monitor premanifest subjects and find patient‐specific drugs. Ann Neurol 2018;00:1–6ANN NEUROL 2019;85:296–301.